2007
DOI: 10.1021/jp068348p
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Characterization of (CH3IO3) Isomers and the CH3O2 + IO Reaction Pathways

Abstract: The geometries, harmonic vibrational frequencies, relative energetics, and enthalpies of formation of (CH(3)IO(3)) isomers and the reaction CH(3)O(2) + IO have been investigated using quantum mechanical methods. Optimization has been performed at the MP2 level of theory, using all electron and effective core potential, ECP, computational techniques. The relative energetics has been studied by single-point calculations at the CCSD(T) level. Methyl iodate, CH(3)OIO(2), is found to be the lowest-energy isomer sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
32
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 42 publications
(93 reference statements)
3
32
1
Order By: Relevance
“…Two of the experimental studies have shown that the reactions RO 2 +IO are fast and may indeed have an important impact on ozone chemistry. Enami et al 13 found the value k= (7. 2 , i.e., it is smaller than the former measurements by about 30 times. The difference is quite large, indicating that the system is very complex.…”
Section: Introductioncontrasting
confidence: 53%
See 3 more Smart Citations
“…Two of the experimental studies have shown that the reactions RO 2 +IO are fast and may indeed have an important impact on ozone chemistry. Enami et al 13 found the value k= (7. 2 , i.e., it is smaller than the former measurements by about 30 times. The difference is quite large, indicating that the system is very complex.…”
Section: Introductioncontrasting
confidence: 53%
“…Several experimental studies reported recently the coupling of IO with the hydrogen peroxy, HO 2 , methylperoxy, CH 3 O 2 , trifluoromethylperoxy, CF 3 O 2 , and ethylperoxy, C 2 H 5 O 2 radicals and measured the corresponding rate coefficients. 2,6,8 These systems are analogous to the reactions of HO 2 and CH 3 O 2 with the ClO and BrO radicals for which several experimental and theoretical studies have been reported. [9][10][11] It was found that the reaction of HO 2 +IO 12 displayed a rate coefficient, k= (8.4±0.3)×10 -11 cm 3 •molecule -1 •s -1 at 298 K and Drougas et al 6 suggested that the HO 2 and IO reaction proceed through the formation of the bound complexes, HOOOI and HOOIO.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…3 and 4). h Updated heats of formation for IO, OIO, and CH 3 O 2 (Dooley et al, 2008;Gómez Martín and Plane, 2009;Knyazev and Slagle, 1998) show that the only accessible exothermic product channel of CH 3 O 2 + IO (Drougas and Kosmas, 2007) is CH 3 O + I + O 2 ( H r = −5 ± 6 kJ mol −1 ), consistent with the high yield of I and low yield of OIO found experimentally (Bale et al, 2005;Enami et al, 2006). Sensitivity studies have been carried out using the preferred rate constant for this reaction of 2 × 10 −12 cm 3 molecule −1 s −1 (Dillon et al, 2006b), resulting in an enhancement of the ozone loss of 0.5% in the MBL and of less than 0.1% integrated throughout the troposphere in the J IxOy scenario, and similarly negligible enhancements in the Base scenario.…”
mentioning
confidence: 99%